EFECTS OF THE PRATICE OF PHYSICAL EXERCISES FOR PREGNANT WOMEN AND CONCEPTUS: DURING AND AFTER THE GESTATIONAL PERIOD (Fiep Bulletin - online, 2015)
From the proposal for preparation of a scientific paper, was made the choice of methodological literature review in order to reflect on the recommendation as to whether physical activities during the gestational period, and thus subsidizing the activities of some health professionals who have trained as pregnant after target audience. Wondered what activities could be carried out by pregnant women as well as duration and intensity, as would be the fetus-placental blood flow during physical activities and physical activities carried out in the gestational period could serve as palliative means the control of pathologies from the gestational period, such as hypertension, gestational diabetes, weight control among others. Response was obtained that the activity more indicated for pregnant women is the walk of moderate level, lasting for 30 minutes with the frequency of 3 times per week. As for the biological and physiological benefits observed in the majority of pregnant women studied and research participants who remained until the end of the same, improving recovery in the post-partum period for pregnant women, improved efficiency in the labor, weight reduction in the case of pregnant women who were overweight, hypertension and elevated ego control due to maintenance of body composition.
Keywords: Physical activity; pregnant women; public health policies.